Development and Language Acquisition of 3-Year-Old Children - Seftiani, Helmi; Khumaeroh, Arni (International Journal of Science and Applied Science: Conference Series, 2023)
This study aims to examine the development and acquisition of language in children aged 3 years. At this age, children show rapid progress in language skills, including the development of vocabulary, grammar, and the ability to communicate more effectively. This research uses a qualitative descriptive approach with direct observation of children aged 3 years in the family environment. The results of the study show that environmental factors, interactions with adults, and language stimulation play an important role in the language development of children aged 3 years. Children at this age begin to master more complex sentence structures, expand their vocabulary, and can communicate more fluently in social situations daily.